Climate-Related Hazards and Internal Migration Empirical Evidence for Rural Vietnam - Michael Berlemann; Thi Xuyen Tran (Economics of Disasters and Climate Change, 2020)
In this paper we employ commune-level data from Vietnam to study whether three types of natural disasters have an impact on emigration figures. We thereby distinguish between temporary and permanent emigration and also differentiate between the effects of recently occurring disaster events and changes in medium-term disaster trends. We find that episodic droughts and flood events tend to cause emigration from the affected communes. While droughts primarily cause temporary migration, flood events tend to induce permanent moves out of the affected regions. Whenever drought or flood events are perceived to have become more severe over the last decade, we also find systematically higher emigration from the affected communes. Episodic typhoons or worsening typhoon trends remain without any significant effect in both the short- and the long-run.
Keywords: 330; Climate change; Natural hazards; Migration; Vietnam